2017
DOI: 10.1039/c6gc02241c
|View full text |Cite
|
Sign up to set email alerts
|

Furfurylamines from biomass: transaminase catalysed upgrading of furfurals

Abstract: A biocatalytic approach using transaminases has been used for the generation of a range of furfurylamines in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 45 publications
2
125
0
Order By: Relevance
“…HMF was purchased from Alfa Aesar (Seoul, Korea), and reduced to BHMF with sodium borohyride following a published method . CDI and other chemicals were purchased from Sigma Aldrich (Yongin, Korea), Tokyo Chemical Industry Co., Ltd. (Seoul, Korea), and Alfa Aesar (Seoul, Korea), and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…HMF was purchased from Alfa Aesar (Seoul, Korea), and reduced to BHMF with sodium borohyride following a published method . CDI and other chemicals were purchased from Sigma Aldrich (Yongin, Korea), Tokyo Chemical Industry Co., Ltd. (Seoul, Korea), and Alfa Aesar (Seoul, Korea), and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…[49,50] For example, Lerchner et al showedt he two-step conversion of isosorbide to the corresponding diamine using an alcohol dehydrogenase and an w-TA. [52] On the other hand, the ability of FgrGaOx to oxidize C-6 hydroxyl groupsong alactosecontaining mono-, oligo-,a nd polysaccharide substrates has been shown to be an efficient way to produce aldehyde-functionalized carbohydrates, [27,28] which might be accepted by w-TAs. [52] On the other hand, the ability of FgrGaOx to oxidize C-6 hydroxyl groupsong alactosecontaining mono-, oligo-,a nd polysaccharide substrates has been shown to be an efficient way to produce aldehyde-functionalized carbohydrates, [27,28] which might be accepted by w-TAs.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Multistep one-pot in vitro enzyme cascades were then established using CnTYR and EfTy rDC,t ogether with av ersatile transaminase from Chromobacterium violaceum (CvTAm) and aw ild-type D29TfNCS enzyme that has been used in some enzyme cascades and demonstrated good substrate tolerances. [16,17,39,40] Initially,t hree cascades were developed using l-tyrosine (4,2 .5 mm ;T able 2, entries 1-3). First the one-pot reaction was developed using CnTYR and EfTy rDC to produce dopamine 2,followed by the addition of phenylacetaldehyde 19 and TfNCS.Itwas necessary to ensure that the TYR and DC reactions were not performed in phosphate buffer, due to the reported competing chemical Pictet-Spengler reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[36] Interestingly,3-F-ltyrosine (9)( 2.5 mm)w as readily accepted, with an 80 % conversion yield (48 h) to give the corresponding F-DOPA analogue 12.Indeed, some previous work has indicated that 9 can be accepted by atyrosinase. [16,17,39,40] Initially,t hree cascades were developed using l-tyrosine (4,2 .5 mm ;T able 2, entries 1-3). Decarboxylated products were readily formed in all cases,g iving 14-18 in 90-100 %c onversion yields,a nd 7 was added to avoid substrate or product oxidation.…”
mentioning
confidence: 99%